PREVENTION OF BULLISHING IN THE SCHOOL ENVIRONMENT UNIT - Suriani; Putri Nazira Sitorus; Yolanda Amalia Sirait; Syasya Khairuna Syibra; Fadya Rahazri Meyfiza; Osama Syahputra Nasution; Gadis Mutiara; Aldi Ardiansyah Siagian; Maya Devira; Uswatun Hasanah Elby (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This service aims to provide insight to students at SMA 4 Kisaran. The background to this service is the Prevention of Bullying in School Environmental Units. Preventing bullying in the school environment is very important to create a learning atmosphere that is safe, comfortable and supports student development. Preventing bullying in the school environment is not only the school's responsibility, but also involves parents, students and society as a whole. The method used in this service is legal education by conveying information regarding laws and regulations related to preventing bullying in the school environment. The results of the activity show that students are very enthusiastic in this activity as seen from several questions asked to the presenters, and it can be concluded that the participants understand the prevention of bullying in the school environment.